ACADEMIC MOBILITY POLICY: ATTEMPT OF CONCEPTUALIZATION - Попій, І. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article is devoted to the problem of academic mobility as a component of educational policy.Based on the analysis of theoretical interpretations and normative provision of academic mobilityregulations, is proposed the interpretation of the concept of «policy of the academic mobility». Theintroduction of this concept info the scientific discourse is justified.